Alpha Lipoic Acid (ALA) Alleviates Hepatocytes Toxicity of Titanium Dioxide Nanoparticles in Rats - Aiman Al-Maathadi; Fardous Karawya; Said Al-Dalaen; Ahmed Aljabali; Anas Satari (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Titanium dioxide nanoparticles (TiO2 NPs) uptake may primarily cause adverse effects by inducing oxidative stress, resulting in cell damage, genotoxicity, inflammation, and immune response. To date, there are limited studies investigating the adverse effect of TiO2 NPs on liver health and no studies found a naturally occurring compound able to ameliorate such effect. Thus, this study investigated alpha lipoic acid (ALA) potential for reversing the biochemical and histopathological changes that TiO2 NPs exposure causes in rat liver.METHODS: Thirty adult male albino rats were divided into: control rats received distilled water, control rats treated with 50 mg/kg ALA, rats intoxicated with TiO2 NPs, and TiO2 NPs-intoxicated rats treated 50 mg/kg ALA. Rats were sacrificed before blood samples were collected to assess the liver function using parameters of alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin, albumin and total protein. Liver tissue homogenates were prepared to assess hepatic antioxidant and oxidative stress using parameters of superoxide dismutase (SOD), catalase (CAT), glutathione (GSH), and malondialdehyde (MDA). Liver tissue sections were used for histopathological analysis and caspase-3 immunohistochemical analysis.RESULTS: TiO2 NPs produced deleterious effects on rat liver tissue, as confirmed through biochemical results, caspase-3 immunohistochemistry, and histological alterations. TiO2 NPs intoxication induced hepatocyte vacuolation, blood vessels congestion, biliary proliferation, apoptosis, and fibrosis. However, ALA treatment of TiO2 NPs-intoxicated rats significantly alleviated deleterious impact on the liver.CONCLUSION: Administration of 600 mg/kg TiO2 NPs to rats resulted in hepatic degenerative lesions, depletion of GSH, oxidative stress, and apoptosis. However, these changes were mitigated by ALA administration. Therefore, ALA offers protection against deleterious effects of TiO2 NPs intoxication.KEYWORDS: titanium dioxide nanoparticles, TiO2 NPs, hepatotoxicity, alpha-lipoic acid (ALA), rat